ANALISIS PENERAPAN ICE BREAKING DALAM MENINGKATKAN KEAKTIFAN SISWA KELAS II PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SD NEGERI 39 PALEMBANG - Novita Sari; Middya Boty; Ines Tasya Jadidah (STKIP Subang, 2026)
This study aims to apply the application of icebreaking in increasing the activeness of second-grade students in Pancasila Education learning at SD Negeri 39 Palem- bang. The background of this study is based on the low activity of students during the learning process, such as lack of attention, participation, and enthusiasm of stu- dents in participating in learning activities in class. The research method used is a descriptive qualitative approach with data collection techniques through observa- tion, interviews, and documentation. The research subjects consisted of teachers and second-grade students of SD Negeri 39 Palembang. The results of the study show that the application of icebreaking is able to create a more enjoyable learning atmosphere, increase concentration, and encourage students to be more active in asking questions, answering questions, and participating in learning activities. The form of icebreaking used is in the form of enthusiastic applause, educational games, songs, and simple movements adapted to the Pancasila Education material. Thus, the application of icebreaking has a positive influence on student activeness in the Pancasila Education learning process.